2017
DOI: 10.18632/oncotarget.18736
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of BNIP3 in pancreatic cancer inhibits the induction of mitochondrial-mediated tumor cell apoptosis

Abstract: Bcl-2 interacting protein 3 (BNIP3) is involved in various cellular processes and is considered a key regulator of hypoxia-induced apoptosis. In the present study, the expression of BNIP3 in pancreatic cancer tissues, the correlation with clinicopathological characteristics and prognosis and the regulation of this protein in pancreatic cancer cell lines with regard to the induction of apoptosis were investigated. BNIP3 expression was significantly lower in pancreatic cancer tissues compared with normal epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 40 publications
(74 reference statements)
4
27
0
Order By: Relevance
“…In accordance with our results, several studies have related BNIP3 silencing with methylation of its promoter as a protective mechanism of cell death in leukemia, pancreatic, and colorectal tumors [10,13,15,18,57,58,60,61], resulting from DNMT1 activity by the mitogen-activated protein kinase in pancreatic cancer [13] and from DNMT1/DNMT3B in colorectal cancer [10]. In most cases, 5-Aza was used to restore normal BNIP3 expression, sensitizing pancreatic cancer cells via hypoxia-mediated apoptosis promotion [13,15,18] and busulfan-resistant myeloid leukemia cells by upregulation of proapoptotic proteins, including BNIP3 [60]. This phenomenon has been largely studied in colorectal cancer, where 5-Aza recovered BNIP3 expression as a biosensitizer pretreatment of irinotecan [61] and to increase chemosensitivity to 5-FU in colorectal cancer [10].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with our results, several studies have related BNIP3 silencing with methylation of its promoter as a protective mechanism of cell death in leukemia, pancreatic, and colorectal tumors [10,13,15,18,57,58,60,61], resulting from DNMT1 activity by the mitogen-activated protein kinase in pancreatic cancer [13] and from DNMT1/DNMT3B in colorectal cancer [10]. In most cases, 5-Aza was used to restore normal BNIP3 expression, sensitizing pancreatic cancer cells via hypoxia-mediated apoptosis promotion [13,15,18] and busulfan-resistant myeloid leukemia cells by upregulation of proapoptotic proteins, including BNIP3 [60]. This phenomenon has been largely studied in colorectal cancer, where 5-Aza recovered BNIP3 expression as a biosensitizer pretreatment of irinotecan [61] and to increase chemosensitivity to 5-FU in colorectal cancer [10].…”
Section: Discussionsupporting
confidence: 93%
“…BNIP3 downregulation has been linked to poorer patient survival and cell proliferation in pancreatic, colorectal, renal, and HCC tumors [10,[12][13][14][15][16][17][18][56][57][58][59]. Erkan et al [14] found lower BNIP3 mRNA levels in an in vitro model and in four out of eight pancreatic cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can also hypothesize that the level of BNIP3 protein modifies the response to some kind of cellular stress and a decrease in the BNIP3 pro-apoptotic protein level in our LHON cell model, could negatively affect apoptosis induction, what in turn can lead to cell survival as in the case of BNIP3-negative cancer cells (He et al, 2017;Li et al, 2017). Our analyses of lymphoblasts with the 11778G>A mutation treated with different concentrations of testosterone could support this hypothesis.…”
Section: Discussionsupporting
confidence: 57%
“…Tumors which showed loss of expression of BNIP3 were found to be more prone to metastases (Koop et al, 2009). Decreased expression of BNIP3 in some cases of cancers was found to be caused by epigenetic modification, hypermethylation, of the BNIP3 promoter (Okami et al, 2004;Lazarini et al, 2012;Li et al, 2017). Treatment of BNIP3-negative pancreatic and colorectal cancer cell lines with a DNA methylation inhibitor restored BNIP3 expression and increased chemosensitivity and cell death in those cell lines (He et al, 2017;Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%